2017
DOI: 10.1002/cphc.201700637
|View full text |Cite
|
Sign up to set email alerts
|

On Atoms‐in‐Molecules Energies from Kohn–Sham Calculations

Abstract: Herein, we discuss three methods to partition the total molecular energy into additive atomic contributions within the framework of Bader's atoms‐in‐molecules theory and in the particular context of Kohn–Sham density functional theory. The first method is derived from the virial theorem, whereas the two other schemes, termed “standard” and “model”, are based on Pendás’ interacting‐quantum‐atoms decomposition. The methods are then compared for a dataset of molecules of interest for direct application in organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 105 publications
0
38
0
Order By: Relevance
“…This has the characteristics of a hydrogen bond, with ∇ 2 ρ b =+0.024 a.u. The small and positive values of the ∇ 2 ρ b at these bcps are indicative of not only significant depletion of charge density at and around the F⋅⋅⋅F and F⋅⋅⋅H bcp regions, but also show these interactions to be closed‐shell in character . These results suggest that QTAIM is sufficiently robust for identifying and characterizing unusual bonding patterns even when the point‐charge model fails to explain instances such as these fluorine‐centered intermolecular complexes.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This has the characteristics of a hydrogen bond, with ∇ 2 ρ b =+0.024 a.u. The small and positive values of the ∇ 2 ρ b at these bcps are indicative of not only significant depletion of charge density at and around the F⋅⋅⋅F and F⋅⋅⋅H bcp regions, but also show these interactions to be closed‐shell in character . These results suggest that QTAIM is sufficiently robust for identifying and characterizing unusual bonding patterns even when the point‐charge model fails to explain instances such as these fluorine‐centered intermolecular complexes.…”
Section: Resultsmentioning
confidence: 85%
“…Charge density and bond path topologies are the two most fundamental signatures of QTAIM that can be used to assist explaining the closed‐shell (attractive) nature of the F⋅⋅⋅F intermolecular distances observed between the fluorine atoms for all the dimers illustrated in Figures 4 and 5. The topology of the charge density ρ (r) generates a faithful mapping of the concepts of the molecular structure hypothesis, the concepts of atoms, bonds, and structure, and a mapping that in addition provides the basis for a theory of structural stability . The demonstration that a molecular structure can be faithfully mapped onto a molecular graph imparts new information to it; nuclei joined by a line in the structure are linked by a line through space along which the charge density, the glue of chemistry, is maximally accumulated .…”
Section: Resultsmentioning
confidence: 99%
“…Although this particular scaling technique is not the only way to recover the total energy of a KS‐DFT calculation with IQA‐like quantities, previous test calculations have shown that it is computationally efficient and gives results that are chemically meaningful and easy to interpret. In this work, we will further explore its usefulness to yield IQA descriptors EnetΩA,EintΩA,ΩB for medium‐sized systems as described by several DFT methods.…”
Section: Methodsmentioning
confidence: 99%
“…Coming back to question 5, it thus appears that some EDAs should not be used to investigate a molecular dataset composed of several different classes. From this point of view, the investigate systems will influence the EDA choice by precluding the use of some of them …”
Section: Question 5: To What Extent Does/can/should Investigated Systmentioning
confidence: 99%